2018
DOI: 10.3389/fevo.2018.00139
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Monogamy in Socially Monogamous Mammals Is Primarily Predicted by Multiple Life History Factors: A Meta-Analysis

Abstract: Background: We still do not understand the key drivers or prevalence of genetic monogamy in mammals despite the amount of attention that the evolution of mammalian monogamy has received. There have been numerous reviews of the hypotheses proposed to explain monogamy, some of which focused on animals in general, while others focused on particular classes like birds or mammals, or on specific orders within a class. Because monogamy is rare in mammals overall but relatively common in some of the orders in which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 87 publications
(123 reference statements)
0
34
1
Order By: Relevance
“…Monogamy is infrequent in mammals and usually occurs in socially monogamous species such as in primates or rodents (Lambert, Sabol, & Solomon, 2018;Ophir, Phelps, Sorin, & Wolff, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Monogamy is infrequent in mammals and usually occurs in socially monogamous species such as in primates or rodents (Lambert, Sabol, & Solomon, 2018;Ophir, Phelps, Sorin, & Wolff, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Female choice likely contributed to the evolution of paternal care (Kvarnemo, 2005;Lukas and Clutton-Brock, 2013;Lambert et al, 2018). Kvarnemo (2005) suggested that if females select males that care for young, this can explain the correlation often observed between paternity and male care but in the opposite direction of causation to that often suggested (i.e., caring males are more likely to sire offspring, rather than males that sire offspring are more likely to provide care).…”
Section: Need For Biparental Carementioning
confidence: 98%
“…Furthermore, even with large litters, a female can compensate for the male's work when he is absent or reduces investment (although at apparent cost to her health and survival, therefore compromising potential future reproductive success) (Sacks and Neale, 2001;Cameron et al, 2011) and females may adjust effort according to litter size (Mech et al, 1999), supporting that male care can be a female preference, rather than pure necessity. Lambert et al (2018) suggested that monogamy and paternal care co-evolved when selection initially favored affiliative males, which subsequently evolved into paternal care.…”
Section: Need For Biparental Carementioning
confidence: 99%
See 2 more Smart Citations